The role of self-esteem, optimism, deliberative thinking and self-control in shaping the financial behavior and financial well-being of young adults - Hashmi, Fatima (2021)
The sustainable financial behavior and financial well-being have been a key concern among the developing societies; thereby encompassing the various psychological factors which play a role in influencing individual’s positive financial behavior and financial well-being, this study is conducted. Research focusing on the psychological aspect of human financial behavior and well-being is scarce, focusing more on the cognitive side such as financial literacy and numeracy. The aim of this research study is to find the role played by the non-cognitive factors such as self-esteem, self-control, optimism and deliberative thinking, in forming the financial behavior and financial well-being of the young adults. A sample of 429 university students from public and private sector was collected via an online and field survey using purposive sampling technique. The survey contained measures for demographics, self-esteem, optimism, deliberative thinking, self-control, general financial behavior and financial well-being. SPSS and PLS-SEM tools were used for the exploration of the relationships among dependent and independent variables. The results of PLS path analysis demonstrate that among the non-cognitive factors, self-control and deliberative thinking show a significant association with both financial behavior, and financial security. Self-esteem plays no significant role in forming the financial behavior of the young adults when all the variables are taken together but it exhibits a significant association with financial well-being (financial security and financial anxiety). Optimism on the other hand exhibits no significant association with both financial behavior and financial well-being (financial security and financial anxiety). The results of this study complement the previous studies and also put forth new outcomes. This research is unique as it is the first of its kind conducted in a consumption-oriented economy like Pakistan. In addition to the previous studies which have often established the link of self-esteem with general well-being, this study goes further by analyzing the association between self-esteem and financial well-being and by the identification of the role played by non-cognitive factors like self-esteem, optimism, deliberative thinking and self-control together on the financial behavior and financial well-being of the individuals using PLS-SEM approach.